Path Analysis on the Life-Course Biopsychosocial Determinants of Stunting in Children Under Five Years of Age in Karawang, West Java - Fauziyyah, Rona Luthfi; Dewi, Yulia Lanti Retno; Wekadigunawan, CSP; Adriani, Rita Benya (Journal of Maternal and Child Health, 2019)
Background: Studies have shown that stunted children are more likely to start school later, perform more poorly on cognitive functioning tests, and are more likely to drop out of school. In future, adults who are stunted as children earn 20% less than comparable adults who were not stunted and are 30% more likely to live in poverty and less likely to work in skilled labor. This study aimed to examine the life-course biopsychosocial determinantsof stunting in children under five years of agein Karawang, West Java, using a path analysis model. Subjects and Method: This was a case control study carried out inTunggakjati, Rengasdengklok, Kutawaluya, Pedes, and Medangasem community health centers, Karawang, West Java, from April to May 2018. A sample of 225 children under five was selected for this study by fixed disease sampling, consisting of 75 stunted children and 150 normal children. The dependent variable was stunting. The independent variables were maternal height, maternal middle upper arm circumference (MUAC), low birthweight (LBW), history of infection illness, maternal education, exclusive breastfeeding, complementary feeding, and family support. Child height was measured by infantometer or microtoice. The other variables were measured by questionnaire. The data were analyzed by path analysis run on Stata 13. Results: Stunting increased with LBW (b=1.64; 95% CI=0.69 to 2.59; p=0.001) and history of infection illness (b=1.80; 95% CI=0.94 to 2.67; p<0.001). Stunting decreased with maternal height ?150 cm (b=-1.57; 95% CI=-2.43 to -0.71; p<0.001) and appropriate complementary feeding (b=-1.80; 95% CI=-2.53 to -1.08; p<0.001). Stunting was indirectly affected by maternal MUAC, maternal education, exclusive breastfeeding, and family support. Conclusion: Stunting increases with LBW and history of infection illness, but decreases with maternal height ?150 cm and appropriate complementary feeding. Stunting is indirectly affected by maternal MUAC, maternal education, exclusive breastfeeding, and family support. Keywords: stunting, life-course, biopsychosocial, children under five Correspondence: